Peningkatan Keterampilan Penggunaan Microsoft Word dalam Penyusunan Surat Resmi bagi Ibu-Ibu PKK - Novita Lestari Anggreini; Tri Pratiwi Olivia Riska Bokings; Ade Yuliana; Dadan Saepul Ramdan; Bagus Salman Alfarizi (Yayasan Pemimpin Inovasi Science, 2026)
The rapid development of information technology requires communities to possess adequate digital literacy skills, particularly in using office applications to support administrative activities. However, many PKK women cadres still have limited knowledge of Microsoft Word and formal letter writing, resulting in less effective administrative document preparation. Therefore, this community service program was conducted to introduce Microsoft Word and formal letter writing to PKK women cadres in Kelurahan Baros, Cimahi City. The program focuses on improving digital literacy, writing skills, and participants' ability to produce proper and well-structured formal documents. The implementation method included preparation, material development, training sessions, and hands-on practice. The results show that the program was successfully implemented, with participants demonstrating high enthusiasm and improved understanding of Microsoft Word features as well as the ability to compose formal letters according to standard writing conventions. This program contributed to enhancing participants' administrative competencies and supporting their daily organizational activities.